In vitro development of Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. isolated from coffee in the presence of chitosan and salicylic acid - Coqueiro, Danila Souza Oliveira; Pedreira, Dandara Porto; Silva, Rômulo Pereira da; Souza, Aline Vaz Laranjeira de; Santos, Arminio (MAGISTRA, 2018)
Abstract: Several factors have contributed to reduced coffee production in Brazil, such as the anthracnose disease (Colletotrichum gloeosporioides). This study aimed to evaluate the effect of chitosan and salicylic acid (SA) on the development of C. gloeosporioides. SA was used at 0, 1.25, 2.5 and 5 mM and chitosan at 0, 1, 2 and 4 mg mL-1. The controls were 10% ethanol (0 mM SA) and 0.05 N HCl (0 mg mL-1 chitosan). Conidia germination was verified using 100 µL from each treatment and 100 µL conidia suspension which were placed in each well of the ELISA plate. After incubated for 24 h the germinated conidia were enumerated. The mycelial growth was evaluated by the transfer of a mycelial disc (9 mm) to the centre of Petri plates containing potato dextrose agar and various concentrations of SA and chitosan. The diameter of the colony was measured daily. Chitosan did not inhibit the germination of conidia (p = 0.397), while SA inhibited up to 58% (5 mM SA) of the germination. There was a significant reduction in the mycelial growth at all SA concentrations, but chitosan was only effective at 4 mg mL-1. Key words: Anthracnose, Antimicrobial, Fungi.